The Concepts of Mudarris, Mu'allim, Murabbi, Mursyid, Muaddib in Islamic Education - Kasmar, Indah Fadilatul; Amnda, Viola; Mutathahirin, Mutathahirin; Maulida, Ana; Sari, Widia Wahana; Kaputra, Soni; Anwar, Fuady; Taufan, Muhammad; Engkizar, Engkizar (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2019)
As it is known that the roles and responsibilities of teachers, especially those teaching Islamic education is enormous. Basically, Islamic Education Teachers teach not only in charge of the subject matter, but also burdened with the responsibility to build learners who have knowledge, morals, have identity, strong character, and has a life skills guidance in accordance with the teachings of Islam. To bear all the burdens and responsibilities required different skills, especially skills as a personal ideal Islamic Education Teachers. In a variety of classical texts, books, literature until recent Islamic educational research found five terms are embedded in referring the teachers, Mudarris, Mu'allim Murabbi, Mursyid, and Muaddib. No articles are discussing a thorough and detailed those five terms in question yet. This article aims to discuss in detail and comprehensively those five terms in Islamic Education Teachers. This research uses the qualitative method with content analysis approach, all data taken from various sources which are derived from classical holy books, books, theories and expert opinion. All data that has been collected are analyzed thematically, in other words the themes that have been obtained are described comprehensively and deeply. Interestingly, the whole themes of the results of this study will be discussed with the results of the study of the researchers earlier and issues of current Islamic Education. The authors hope that this article can be a source of guidance for Islamic Education teachers to becoming an ideal individual, besides that it can also be a basis for the next researchers to discuss this problem in different contexts and issues.